2011
DOI: 10.1101/cshperspect.a004796
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides in Cell Architecture

Abstract: Inositol phospholipids have been implicated in almost all aspects of cellular physiology including spatiotemporal regulation of cellular signaling, acquisition of cellular polarity, specification of membrane identity, cytoskeletal dynamics, and regulation of cellular adhesion, motility, and cytokinesis. In this review, we examine the critical role phosphoinositides play in these processes to execute the establishment and maintenance of cellular architecture. Epithelial tissues perform essential barrier and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
159
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 134 publications
3
159
0
Order By: Relevance
“…This tight control of PIP3 levels is likely to be extremely important as PIP3 regulates a wide variety of cellular processes including growth, proliferation and apicobasal organization (Shewan et al, 2011;Vanhaesebroeck et al, 2012). The absence of Pten from DC and wound leading edges permits PIP3 to become elevated specifically in these locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tight control of PIP3 levels is likely to be extremely important as PIP3 regulates a wide variety of cellular processes including growth, proliferation and apicobasal organization (Shewan et al, 2011;Vanhaesebroeck et al, 2012). The absence of Pten from DC and wound leading edges permits PIP3 to become elevated specifically in these locations.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K catalyses the phosphorylation of phosphatidylinositol 4,5-bisphosphate [PIP2; PtdIns(4,5)P 2 ] to yield PIP3 while Pten catalyses the reverse reaction, dephosphorylating PIP3 to PIP2. Phosphoinositides are also known to regulate the assembly and apicobasal organization of cell-cell junctions in epithelia, and both PI3K and Pten can associate with cell junction (Kovacs et al, 2002;Shewan et al, 2011;von Stein et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This pathway was described as being responsible for stimulating protein kinase (PK) activation, including mitogen-activated kinase protein (MAPK), which has been previously reported as an attendee in the regulation of oocyte meiotic resumption, in which it may act directly or indirectly [9]. Recent studies have shown that MAPK is required in gonadotropininduced meiotic resumption [35,38,39,44]. Other studies have also established that MAPK as well as protein kinase A (PKA) interrupts the communication between the CCs and the oocyte, thus decreasing the cyclic adenosine Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylinositol phosphates (PIPs) are important for actin cytoskeleton organization, vesicle trafficking (exo-and endocytosis) and transcription -all of which are required for polarized cell growth (Di Paolo and De Camilli, 2006;Strahl and Thorner, 2007;Vicinanza et al, 2008;Kwiatkowska, 2010;Saarikangas et al, 2010;Shewan et al, 2011). The phosphatidylinositol PtdIns(4,5)P 2 is a major PIP species, generated by phosphorylation of PtdIns(4)P at position 5 by type I phosphatidylinositol-4-phosphate 5-kinases (PI4P5K).…”
Section: Introductionmentioning
confidence: 99%